Acceptable risk and life and death decisions: a case study. Issue 1 (1st May 2014) - Sherman, Cherie Ann; Anderson, Philip M.
Abstract : Case description: This case discusses the best-selling security system for preventing shoplifting and the dilemma its startup manufacturer faced when it learned there was a very remote possibility that the system might interfere with heart pacemakers. The theme of the case is that when health is involved, a company must carefully consider any level of preventable risk a product poses, even if that level of risk is extremely low.